Anti Inflammatory Activity Test of Ethanol Extract of Fennel Leaves and Fruits (Foeniculum Vulgare Mill.) In Wistar Rats - Ahwan Abdul (Journal of Nutraceuticals and Herbal Medicine, 2020)
Fennel plant has various kinds of benefits such as anti-inflammatory. Fennel plants contain alkaloid compounds, flavonoids, saponins, polyphenols, tannins, anthraquinones, and steroids. The research objective was to determine the anti-inflammatory activity of the ethanol extract from fennel leaves and fruit. The research method belongs to experimental research with edema formation on rats' feet induced by 1% carrageenan. The animals' tests were randomly divided into eight treatment groups and measured the volume of their feet. Each group was given CMC Na 1% (negative control), diclofenac sodium 4.5mg/Kg weight rats (positive control), and ethanol extract of fennel leaves and fruit at a dose of 87.5 mg/Kg rat body weight, 175 mg/ Kg rat body weight, 350 mg/Kg rat body weight. Moreover, the animals' tests were induced with carrageenan 1% while the edema volume of rat leg was measured at the hours of 0.25; 0.5; 0.75; 1; 1.25; 1.5;1.75; 2.00 after induction of carrageenan. The results of the study were edema volume data and AUC value for each treatment. The data were analyzed using the Kolmogorov-Smirnov (normality test), Levene test (homogeneity test), and One-Way Anova (effectiveness test). The normality and homogeneity test results show that there is no significant difference (P0.05). In contrast, the effectiveness test between CMC Na 1% (negative control) and Diclofenac sodium 4,5 mg / Kg weight (positive control) shows the significant result (P0.05), CMC Na (negative control) and all extract treatment shows the insignificant result (P0.05), Diclofenac Natrium 4,5 mg/ Kg weight (positive control) with all treatments indicates the significant result (P0.05).